Pengaruh Investasi, Jumlah Wisatawan, dan Belanja Modal Terhadap Pendapatan Asli Daerah Kabupaten/Kota Se-Jawa Tengah - Suci Nasehati Sunaningsih; Agustina Prativi Nugraheni (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Regional autonomy has consequences for local governments to achieve regional independence in governance affairs. An indicator of regional financial independence is Original Local Government Revenue (OLGR). This study aims to analyze the effect of investment, number of visitors, and capital expenditures on OLGR in Regency/City Governments in Central Java for the period 2017-2020. The year 2020 was the initial period of the Covid-19 pandemic which had a huge impact on national economy. The sample in this study consisted of 29 regencies and 6 cities in Central Java Province. Data analysis methods include: descriptive analysis, estimate the estimation model, classical assumption test, and hypothesis testing. The results showed that the investment and number of visitors has no positive and significant effect on OLGR, while the capital expenditure has a positive and significant effect on PAD. All variables in this study simultaneously affect OLGR. By the results of this study, Regency/City Governments in Central Java Province could be optimizing the effectiveness and efficiency of using capital expenditure so it can be useful for increasing OLGR.